PENERAPAN PEMBELAJARAN TEMATIK DI MASA PANDEMI COVID19 MELALUI MODEL PROBLEM BASED LEARNING DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS IV SD - Yuanita Dewi Chrisnamurthy; Ika Septiana; Elis Dwi Purbiyanti (Universitas Negeri Medan, 2021)
Abstract: Application Of Thematic Learning In The Time Of The Covid 19 Pandemic Through The Problem Based Learning Model In Increasing The Learning Outcomes Of Students In Class IVElementary School. The use of the right model in the teaching and learning process will create an active learning atmosphere, not only focused on teacher activities, but also on student activities. In the teaching and learning process, a teacher is expected to be able to carry out his duties and functions as a teacher and be able to apply models that are in accordance with the material so as to improve student learning outcomes. The formulation of the problem in this study is how are student learning outcomes on the theme of the richness of my country by applying a problem based learning model for the fourth grade of SD Muhammadiyah 17?. This research uses classroom action research (CAR). Data were collected through (1) student observation sheets, (2) learning outcomes test questions using percentage formula analysis. Based on the results of the analysis of research data, it was found that (1) student activities in the first cycle of 67.04% were in the (enough category), increased in the second cycle by 78.40% (good category), and increased in the third cycle by 92.04 % (very good category). (2) Student learning outcomes in the first cycle were 69.38% (enough category), increased in the second cycle by 76.84% (good category), and increased in the third cycle by 86.84%. Thus, it can be concluded that the application of the Problem Based Learning model in improving student learning outcomes on the theme of the richness of my country in the fourth grade of SD Muhammadiyah 17 has been achieved.Keywords: Learning Outcomes, Problem Based LearningAbstrak: Penerapan Pembelajaran Tematik Di Masa Pandemi Covid 19 Melalui Model Problem Based Learning Dalam Meningkatkan Hasil Belajar Peserta Didik Kelas IV SD. Penggunaan model yang tepat dalam proses belajar mengajar akan menjadikan suasana belajar yang aktif, tidak hanya terfokus pada aktivitas guru, tetapi juga pada aktivitas siswa. Dalam proses belajar mengajar, seorang guru diharapkan mampu melakukan tugas dan fungsinya sebagai guru dan mampu menerapkan model yang sesuai dengan materi sehingga dapat meningkatkan hasil belajar siswa. Rumusan masalah dalam penelitian ini adalah Bagaimanakah hasil belajar siswa pada tema kayanya negeriku dengan menerapkan model problem based learning kelas IV SD Muhammadiyah 17?. Penelitian ini menggunakan metode penelitian tindakan kelas (PTK). Data dikumpulkan melalui (1) Lembar observasi siswa, (2) Soal tes hasil belajar dengan menggunakan analisis rumus persentase. Berdasarkan hasi analisis data penelitian didapatkan bahwa (1) Aktivitas siswa pada siklus I sebesar 67,04 % berada pada (katagori cukup), meningkat pada siklus II sebesar 78,40% (katagori baik), dan meningkat pada siklus III sebesar 92,04% (kategori baik sekali). (2) Hasil belajar siswa pada siklus I sebesar 69,38 % (katagori cukup), meningkat pada siklus II sebesar 76,84% (katagori baik), dan menngkat pada siklus III sebesar 86,84%. Dengan demikian dapat disimpulkan bahwa Penerapan model Problem Based Learning dalam meningkatkan hasil belajar siswa pada tema kayanya negeriku kelas IV SD Muhammadiyah 17 sudah tercapai.Kata Kunci: Hasil Belajar, Problem Based Learning